Determinación de los factores predominantes en la publicidad de la marca Sybilla: estudio de caso con el sector femenino de los niveles socioeconómicos A y B en Lima. - Zárate Galvez, Adriana Eliana (2020)
To carry out the following research, three objectives were set. It is one general objective and two specific ones. The general objective is to determine the predominant factors in Sybilla's advertising strategy in Lima. This study was carried out from the perspective of consumers in sectors A and B. The two specific objectives are First, identify the main advertising factors of the Sybilla brand according to its target audience. In short, what does this brand do to attract its consumers. Second, to compare the strategies through which Sybilla sought to position itself in the market between 2016 and 2018. To achieve this second objective, we will focus on analyzing the advertising strategies used on Facebook by Sybilla in 2016, 2017 and 2018. The first objective will serve to evaluate the perspective of the population chosen to carry out this thesis. The second objective seeks to analyze and identify the advertising strategies used by the Sybilla brand to generate and strengthen ties with its customers.